“Evaluación del hematocrito en bovinos de la ganadería FACIAG-UTB tratados con auto hemoterapia en 2 dosis” - Torres Villamar, Evelin Jamileth (2023)
Auto hemotherapy is recognized as an alternative treatment, even naturopathic, due to the lack of information that places it as an important treatment for medicine, both human and veterinary medicine. Auto hemotherapy was created by Dr. Paul Revaut in 1911, the technique that consists of the extraction and subsequent inoculation of the same blood from the patient to be treated, that is, autologous blood. The present investigation was carried out in order to provide scientific data that help give the importance it deserves to this technique, which are extremely scarce or non-existent. The purpose of this research was to evaluate the hematocrit in cattle from the FACIAG UTB farm treated with autohemotherapy in 2 doses, 15ml and 20ml. The treatments were carried out in 12 bovines, divided into two groups, 6 bovines for the 15 ml dose, and 6 bovines for the 20 ml dose, of the 6 bovines, one of them was chosen as a control, that is, a control by each group. To know what the results were, blood tests were carried out, by means of complete blood counts. The design that was used was completely randomized, with 2 treatments and 5 repetitions, by means of the statistical test of comparison of the Tukey mean at 5%. According to the results obtained, the treatment with the 15 ml dose, nor the treatment with the 20 ml dose, demonstrated numerical significance in the bovine females of the FACIAG UTB, apparently healthy